Fundamentals of lightning - Rakov, Vladimir A (Cambridge University Press, 2016)
"It presents the current state-of-the-art in lightning science including areas such as lightning modeling, calculation of lightning electromagnetic fields, electromagnetic methods of lightning location, and lightning damaging effects and protective techniques. Pedagogical features designed to facilitate class learning include end-of-chapter summaries, further reading suggestions, questions and problems, and a glossary explaining key lightning and atmospheric electricity terms. A selection of appendices are provided at the end of the book, which include detailed derivations of exact equations for computing electric and magnetic fields produced by lightning"--